Searching for the "Productivity Slowdown": Some Surprising Findings from West German Manufacturing - Flaig, Gebhard; Steiner, Viktor (The Review of Economics and Statistics, 1993)
The authors test the hypothesis of a negative long-term trend and/or a structural break in total factor productivi ty after the first oil price shock for West German manufacturing industries within an econometric model based on a flexible cost function with capital as a quasi-fixed factor. After adjusting total factor productivity growth for scale economies and varying capacity utilization, this hypothesis is not supported by their empirical findings for the grea t majority of industries studied, whereas the hypothesis that the (log-)level of total factor productivity follows a random walk with drift is not rejected by various statistical tests. Copyright 1993 by MIT Press.